Development of IoT Application for Lake Surface Cleaning Machine - Lim, Wei Hang; Kok, Boon Ching (Evolution in Electrical and Electronic Engineering, 2023)
This paper focuses on developing an Internet of Things (IoT) application for a lake surface-cleaning machine. The goal is to contribute to a cleaner environment by integrating IoT technology into the machine. Raspberry Pi is used as the microcontroller to control all the sensors and to run the OpenCV for the object detection algorithm. Meanwhile, an infrared sensor is used to detect the specific situation to trigger the alert system while the Euclidean Distance is used to calculate the shortest distance from the charging station. The findings have illustrated the successful achievement of the project objectives, showcasing the effectiveness of the object detection algorithm, designing an efficient alert system and achieving good energy conservation. By leveraging IoT technology, the machine can autonomously detect and remove garbage from the lake surface, saving time and energy for individuals involved in the cleaning process. The alert system ensures timely actions in response to full garbage tanks, low energy storage, and fully charged energy storage, enabling authorized personnel to take appropriate measures promptly. Moreover, the machine's energy conservation measures, such as calculating the shortest path to the charging station and triggering the conveyor when necessary, enhance operational efficiency and minimize energy consumption. Overall, the research outcomes highlight the significance of IoT applications in combating lake pollution and fostering a cleaner environment.